N, N, N’, N’-Tetramethy -p- phebylebediamine dihydrochloride) as a New Analytical Reagent for Spectrophotometric Determination of Iron (III). (Fadhil M. Najib & Nawzad N. Ahmad) - Najib, Fadhil M.; Ahmad, Nawzad N. (Sulaimani Journal for Pure and Applied Sciences, 1997)
new reagent N, N,-N,-N - Tetramethyl-pe phenylenediamine dihydrochloride (TMPDA-2HCl) was described for the determination of Iron (II) spectrophotometrically. Beer's Law was obeyed between (0.4- 2.4 ppm) Iron (III). Optimum conditions were : pH(2-3), λmax= 560 nm, 2ml (0.001M) reagent freshly prepared for final 25ml solution containing 10 to 60 μg [i .e. 0.4-2.4 ppm Fe(III)], color develops after 10 minutes and remains stable for three hours. Best Straight line drawn by the method of least square gave correlation coefficient of (0.999) between (0 - 2 ppm). At lower limit of Fe(III) determination (0.4 ppm), maximum error did not exceed 5% in the presence of accumulative interfering ions with coefficient of variation of 1.8% there values, for 2 ppm Fe(III), were less that 4% and 0.34% respectively. Average extinction coefficient was about (1.5 x 10^4 L.mol-1. cm-1). The Stoichiometry of the complex [ Fe(III) - R ] was 1:1. Interferences of 27 ions were studied for their tolerance levels. Only few ions interfered seriously which were Cu2+, Ag+, Zn2+, Sn2+, C2O42-, and F-.